Lucia Thesen (2024). Knowledge-making From a Postgraduate Writers’ Circle: A Southern Reflectory. Multilingual Matters - Faerber, Jonathan (Discourse and Writing/Rédactologie, 2025)
Although writing can be a form of knowledge and knowledge-making, it is far from the only way postgraduates create and exchange knowledge. A recent book by Lucia Thesen details several ways in which a writing group at the University of Cape Town anticipates and responds to dominant constructions of knowledge and time within the academy. Ultimately, her discussion illuminates the possible benefits for students when writing interventions are conceived as an alternative to usual forms of assessment and knowledge rather than an instrument used in service of a narrow view of scholarly traditions.